The Relationship Between Smartphone Addiction and Academic Procrastination in Final-Year Students - Alvin Ardhi Wijaya; Enjang Wahyuningrum (Jurnal Multidisiplin Sahombu, 2026)
The increasing use of smartphones among students may affect their learning focus and encourage procrastination. This study aims to determine the relationship between smartphone addiction and academic procrastination among final-year students. The research employed a quantitative correlational method with purposive sampling as the sampling technique. Data were analyzed using Spearman’s rho test. The results show a significant positive relationship between smartphone addiction and academic procrastination (p = 0.000 < 0.05). This indicates that the higher the level of smartphone addiction, the greater the students’ tendency to procrastinate academically.